Accessible by Design: An Opportunity for Virtual Reality - Mott, Martez; Cutrell, Ed; Gonzalez Franco, Mar; Holz, Christian; Ofek, Eyal; Stoakley, Richard; Morris, Meredith Ringel (ISMAR 2019 Workshop on Mixed Reality and Accessibility, 2019)
Too often, the accessibility of technology to people with disabilities is an afterthought (if it is considered at all); post-hoc or third-party patches to accessibility, while better than no solution, are less optimal than interface designs that consider ability-based concerns from the start. Virtual Reality (VR) technologies are at a crucial point of near-maturity, with emerging, but not yet widespread, commercialization; as such, VR technologies have an opportunity to integrate accessibility as a fundamental, developing cross-industry standards and guidelines to ensure high-quality, inclusive experiences that could revolutionize the power and reach of this medium. In this position paper, we discuss the needs, opportunities, and challenges of creating accessible VR.